THE LEVEL OF KNOWLEDGE AND APPLICATION OF ANIMAL WELFARE PRINCIPLES BY K-9 HANDLERS AT THE DIRECTORATE OF ANIMAL POLICE KORSABHARA BAHARKAM POLRI - Gabriella Panyuwa; Hamong Suharsono; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
K-9 handlers at the Directorate of Animal Police, Korsabhara Baharkam Polri, play a crucial role in ensuring the welfare and adequate knowledge related to the K-9s under their care. The importance of surveying the level of knowledge and the implementation of animal welfare principles by K-9 handlers becomes evident to ensure that these animals' lives adhere to ethical and welfare standards. The aims of this study is to assess the level of knowledge of K-9 handlers at the Directorate of Animal Police, Korsabhara Baharkam Polri, regarding animal welfare principles and to evaluate the extent to which these principles are applied. The method employed is a survey involving 40 respondents, consisting of 10 K-9 handlers from each of the four different units: general tracking, explosives, search and rescue (SAR), and narcotics. The collected data were analyzed qualitatively using a descriptive approach and presented as percentages in tables. The results indicate that the level of knowledge of K-9 handlers regarding animal welfare is classified as good, with an average score of 73.59%. Meanwhile, the implementation of animal welfare principles reaches an average of 90.05%, with the highest implementation in the aspect of freedom from fear and distress (96%) and the lowest in the aspect of freedom from discomfort (79.6%). The level of knowledge and application of animal welfare in the aspect of freedom from discomfort needs to be further improved.